DETERMINANTS OF URBAN ROADSIDE TRADING IN ENUGU METROPOLIS - Juliet Ibekwe; Anierobi, Christopher M. (IJRDO - Journal of Social Science and Humanities Research, 2020)
Roadside trading is still a current issue in the city of Enugu despite location of markets and government regulations. Presently, the city is witnessing an unprecedented increase in the influx of commercial activities particularly at the major roads. The ensuing competition for space at strategic and easily accessible location for display of goods for customers often results to the prevalent incessant traffic obstructions in the city. This indiscriminate display of goods has resulted in road obstructions, disorderliness of land uses and land use conversions, traffic congestion, littering and blockage of drainage channels, abuse and misuse of facilities, increased noise pollution, encroachment and reduction in the width of access roads, poor and inadequate parking, increased visual intrusion and social vices among many others. There is therefore the need to look into the activities of road side trading in the city for insight into its persistence. This study therefore aims at empirically determining the factors influencing the proliferation of roadside trading in Enugu urban centre with a view to proffering suitable policy measures to curb it. The survey research design was adopted in this study. Both primary and secondary data were utilized. A sample size of 950 was determined and this informed the distributed research questionnaire across selected urban neighbourhoods that have high volume of roadside trading activities as identified by the study in each of the three residential densities of Enugu city. The Principal Component Analysis (PCA) was used to analyse and test the research hypothesis. Findings indicated that four influential factors including location, economic, accommodation, and social factors were the determinants of roadside trading in Enugu metropolis. Major recommendations include proper enforcement of policy measures on land use regulations and road decongestion among others.